2016
DOI: 10.5213/inj.1630504.252
|View full text |Cite
|
Sign up to set email alerts
|

Electroanatomical Mapping of the Urinary Bladder

Abstract: A noncontact mapping system (EnSite) was used for electroanatomical mapping of the bladder simultaneously with pressure flow study in three women with lower urinary tract symptoms. We selected the periods of obvious detrusor activity. Data were processed to remove baseline drift, and an envelope of electrovesicography (EVG) data was created. The correlation coefficient for the correlation between between the EVG envelope and the detrusor pressure (Pdet) was calculated. Bladder geometry was successfully created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…In this work we use cardiac electrophysiology catheters and needle electrodes to provide quantitative values regarding propagation velocities, pacing threshold, activation patterns, and refractory time in the ureteric smooth muscle. Our study extends the results of two previous studies which provided qualitative insight on the use of commercially available cardiac electrophysiology equipment for detecting electrical activity in the urinary smooth muscle (bladder). To the best knowledge of the authors, the present work is the first in the lower urinary tract to: i) provide quantitative measurements of propagating electrical activity by means of catheter‐based electrodes, in a well‐defined ex vivo stimulation protocol; and ii) compare those recordings with conventional needle electrodes.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In this work we use cardiac electrophysiology catheters and needle electrodes to provide quantitative values regarding propagation velocities, pacing threshold, activation patterns, and refractory time in the ureteric smooth muscle. Our study extends the results of two previous studies which provided qualitative insight on the use of commercially available cardiac electrophysiology equipment for detecting electrical activity in the urinary smooth muscle (bladder). To the best knowledge of the authors, the present work is the first in the lower urinary tract to: i) provide quantitative measurements of propagating electrical activity by means of catheter‐based electrodes, in a well‐defined ex vivo stimulation protocol; and ii) compare those recordings with conventional needle electrodes.…”
Section: Discussionsupporting
confidence: 83%
“…Since needle electrodes always had contact with the tissue, the latter point would mainly involve the cardiac catheters, where it is more difficult to assess the contact between electrode and tissue. Contactless recordings were shown in the urinary tract by Frag et al, however the amplitude of the signals may be different between contact and contactless recordings (most probably lower amplitudes are associated with contactless recordings) and may justify our unsuccessful recordings using cardiac catheters. Catheter design could be optimized to improve electrode‐tissue contact (e.g., catheters with inflatable balloon).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, a recent study showed a good correlation between pressure flow studies and BVE in women . Moreover, a BVE <60% is commonly used to define DU . Therefore, we believe that the BVE of 48% in the aged female rats used in this study is a robust indicator of DU.…”
Section: Discussionmentioning
confidence: 57%
“…17 Moreover, a BVE <60% is commonly used to define DU. 18 Therefore, we believe that the BVE of 48% in the aged female rats used in this study is a robust indicator of DU.…”
Section: Discussionmentioning
confidence: 73%